Day 1 Tue, August 11, 2015 2015
DOI: 10.2118/174586-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Injection and Its Seepage Mechanism of Polymer Flooding in Heterogeneous Reservoirs

Abstract: Field application proves that polymer flooding is an effective technology for improving development effect of heterogeneous reservoirs. Previously, single slug injection is performed. However, there are problems of profile reverse, non-effective circulation of polymer solution in high permeability zone, over much polymer dosage and so on. Thus a new technique of alternative injection for improving oil displacement effect of polymer flooding is developed. Some oil displacing experiments with different injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The exact number of polymer slugs which provides the best result will be investigated in this section. A number of alternative cycles starting from 1 to 5 cycles as recommended by previous literature [5] are simulated with the same polymer mass and bulk polymer slug is segregated equally as illustrated in Fig. 7.…”
Section: E Number Of Alternative Cyclesmentioning
confidence: 99%
“…The exact number of polymer slugs which provides the best result will be investigated in this section. A number of alternative cycles starting from 1 to 5 cycles as recommended by previous literature [5] are simulated with the same polymer mass and bulk polymer slug is segregated equally as illustrated in Fig. 7.…”
Section: E Number Of Alternative Cyclesmentioning
confidence: 99%
“…The reserves of heavy oil resources in China are also considerable [1]. The heavy oil resources with underground crude oil viscosity of 150~1000 mPa•s in the Bohai oilfield are of great percentage [2,3]. At present, the heavy oil reservoirs in Bohai oilfield are mainly developed by conventional water flooding, which generally has poor development effect and low reserve recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Peihui and Haibo [5] performed laboratory experiment to identify the effect of alternative polymer injection comparing to single-slug injection in aspects of overcoming profile reverse and ineffective polymer circulation in high permeability layer. Two scenarios were designed; single-slug injection was performed to inject only one polymer slug as a base case, alternative injection was accomplished by injecting alternative polymer slugs of high viscosity and low viscosity; more cycles, less polymer viscosity.…”
Section: Polymer Flooding In Multilayered Reservoirmentioning
confidence: 99%
“…Since a bulk polymer slug can be separated into several smaller slugs with water slug in between to increase polymer injectivity, the exact number of polymer slugs which provides the best result will be investigated in this section. A number of alternative cycles starting from 1 to 5 cycles as recommended by previous literature [5] are simulated with the same polymer mass and bulk polymer slug is separated equally as illustrated in Figure 5.24. From the results of 1,250 ppm cases, it can be observed that to select either three, four or five cycles provides very similar oil recovery of 52.34%, 52.3% and 52.28% respectively also, with the same production time of 1,886 days.…”
Section: Effect Of Number Of Alternative Cyclesmentioning
confidence: 99%